BFFT quantization and dynamical solutions of a fluid field theory - Natividade, C. P. [UNESP]; Boschi-Filho, H. (American Physical Society (APS), 2000)
We study a field theory formulation of a fluid mechanical model. We implement the Hamiltonian formalism by using the BFFT conjecture in order to build a gauge invariant fluid field theory. We also generalize previous known classical dynamical field solutions for the fluid model. ©2000 The American Physical Society.